PRÓ/PET-SAÚDE III e o perfil formativo do odontólogo - Freire, Cláudia Patrícia de Lima (2014)
This research discusses the formation issues in Odontology in the National Program of Formation Reorientation in Health together with the Educational Program Working for Health (Pró/PET-Saúde III 2012-2014), which has as general objective the investigation of the changes in formation profile of the Odontology student of the Federal University of Alagoas (UFAL), from the participation of the course in this program. The research was qualitative and occurred in two stages: first, the reading was done to contextualization of the National Curriculum Guidelines for Health and Odontology, National Policy of Permanent Education in Health, Educational Curriculum Proposal for the Odontology Course of UFAL, and projects and Pró/PET-Saúde III reports; in the second stage, the focal group was conducted with a tutor, preceptors and Odontology students participants of the Pró/PET-Saúde III from the UFAL Campus, Maceió. To conduce the focal group, a script was used with guiding questions related to the formation profile in Odontology, formation in Odontology and the participation in the Pró/PET-Saúde III. After obtaining the data, they were transcribed, read and an analysis was performed by categories. We conclude that the participation in programs for Formation Reorientation appears as an alternative to reduce the imbalance existent between that which is desired and what exists in the forming context in Odontology and what the Pró/PET Saúde III contributes to in the practice for the effectiveness of a Formative Profile in Odontology consistent with the proposals of SUS, of the National Curriculum Guidelines for Odontology and of the National Policy of Permanent Education in Health even though advances in the political and collective discussions of these proposals are needed.